Pengembangan Buku Saku Berbasis Ideal Problem Solving terhadap Kemampuan Pemecahan Masalah pada Materi Bangun Ruang - Balqis, Puri Ratih; Sandie, Sandie; Jamilah, Jamilah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of the research is to develop a Pocket Book based on IDEAL Problem Solving that is suitable for use by students. This research is Research and Development (R&D). The research design used is the ADDIE model which consists of five stages consisting of Analysis, Design, Development, Implementation and Evaluating. This research was conducted at Assalam Pontianak Middle School with the research subjects being 15 students in class VII B. The data collection tools used were expert validation sheets, teacher and student response questionnaires, and problem solving ability tests. The data analysis used is calculating the validity of the media with the minimum criteria of